2016
DOI: 10.1186/s12885-016-2284-3
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A2 – a novel genetic marker for early aromatase inhibitor response in the treatment of breast cancer patients

Abstract: BackgroundEndocrine resistance is a major obstacle to optimal treatment effect in breast cancer. Some genetic markers have been proposed to predict response to aromatase inhibitors (AIs) but the data is insufficient. The aim of the study was to find new genetic treatment predictive markers of AIs.MethodsThe ongoing population-based BC-blood study in Lund, Sweden includes women with primary breast cancer. This paper is based on AI-treated patients with estrogen receptor positive tumors who underwent breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…Cigarette smoke may also interact with therapy through upregulation of cytochrome P 450 enzymes such as CYP1A2 that is involved in both metabolism of oestrogens and AIs ( Grimm and Dyroff, 1997 ; Schrenk et al , 1998 ; Tsuchiya et al , 2005 ; Kamdem et al , 2011 ). Moreover, CYP1A2 genotypes predicted short-term prognosis in AI-treated patients from a subset of this cohort ( Simonsson et al , 2016 ). If cigarette smoke interacts with AIs, smokers assigned to AIs should be encouraged to quit.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke may also interact with therapy through upregulation of cytochrome P 450 enzymes such as CYP1A2 that is involved in both metabolism of oestrogens and AIs ( Grimm and Dyroff, 1997 ; Schrenk et al , 1998 ; Tsuchiya et al , 2005 ; Kamdem et al , 2011 ). Moreover, CYP1A2 genotypes predicted short-term prognosis in AI-treated patients from a subset of this cohort ( Simonsson et al , 2016 ). If cigarette smoke interacts with AIs, smokers assigned to AIs should be encouraged to quit.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 91 SNPs to include in the analyses based on our previous study [ 14 ] and other published studies that identified genes related to estrogen and inflammation pathways [ [12] , [13] , [14] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. Participant DNA was extracted from buffy coat specimens using the Qiagen QiaAmp 96 DNA Blood Kit (Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…This study is based on 1,116 patients who were included in a prospective cohort of primary breast cancer patients (BC‐Blood Study) at the Skåne University Hospital in Lund, Sweden that has been previously described in depth . The patients in the present study were included between October 2002 and June 2012, were between 24 and 99 years of age, and did not have any history of cancer during the past 10 years.…”
Section: Methodsmentioning
confidence: 99%